Exploring the Pool of Pathogenic Variants of Amelogenesis Imperfecta: An Approach to the Understanding of Its Genetic Architecture - Blanca Urzúa (Frontiers Media S.A., 2021)
Objective: To identify which genes are associated with the clinical phenotype of amelogenesis Imperfecta (AI) and to elucidate which of these genes participate in the determination of isolated and syndromic forms.Methods: In this review, all data on mutations described in AI-related genes were obtained from HGMD® Professional. The data in relation to the mutations, inheritance, phenotype, type of AI and country were supplemented with information from the literature. The identity codes and frequency values were obtained from the dbSNP, ClinVar and OMIM databases. The percentage of specificity (PE) was determined for each gene.Results: HGMD® describes 27 genes involved in AI, which we propose to group into 5 categories: (1) genes whose mutations are associated only with isolated AI, (2) genes whose mutations cause only syndromic AI, (3) genes with both mutations that cause isolated AI and mutations responsible for other pathologies, (4) genes with mutations responsible for syndromic AI and mutations that cause other pathologies, and (5) genes with mutations that cause isolated AI and mutations that cause AI associated with syndromes and other pathologies. Using the PE calculation, the genes were ranked into 5 specificity groups. The genes of category 1 are specific for isolated AI, while the genes of categories 2 and 4 are non-specific. Interestingly, we observed that mutations in some genes were associated with different types of cancer.Conclusion: The ACP4, AMTN, MMP20, ODAPH, RELT, SLC24A4 and SP6 genes participate in causing isolated AI, and the CNNM4, DLX3 and FAM20A genes participate in causing syndromic forms of AI.